Factors that influence person organization fit in Suruhanjaya Koperasi Malaysia Negeri Sembilan (SKM) / Nur Liyana Mohd Nazri and Nor Shakira Othman - Mohd Nazri, Nur Liyana; Othman, Nor Shakira (Faculty of Business and Management, 2015)
This research is to study on factors that influences person organization fit in Suruhanjaya Koperasi Malaysia (SKM) at Negeri Sembilan. This study aim on four factors that influences person organization fit which are organization support, job satisfaction, psychological ownership and working environment. A good person organization fit is important in order to retain employees in the organization. Organization support, job satisfaction, psychological ownership, and working environment will be discussed to see if it will affect person organization fit. In this research, it includes sixty respondents from different age, working length, job position and department. Data was collected through questionnaire that had been distributed to the respondents in Suruhanjaya Koperasi Malaysia Negeri Sembilan. Result of the present research shows that there was significant relationship between working environment and person organization fit. This study also used regression analysis to identify which of the factors that had most been influence towards person organization fit. This study is beneficial to the company as it could help person fit with the organization. Recommendations for the future also have been discussed.